Utilization of mechanical compression as a disinfestation technique for Hessian fly (Mayetiola destructor (say)) in timothy hay: Field test - Tabil, Lope G.; Talebi, S.; Shaw, M. D.; Crerar, W. J. (International Journal of Agricultural and Biological Engineering, 2011)
Baled timothy hay underwent testing at a hay processing plant in Canada to determine if mechanical compression (rebaling) could be used as a disinfestation protocol for Hessian fly (Mayetiola destructor (Say)) puparia. ?Pressure sensitive films were randomly placed throughout the hay material, on the chamber walls, and in different orientations, to assess the hay compaction unit